Review Kepemimpinan Vladimir Putin Dalam Kebijakan Pertahanan Rusia Berdasarkan Teori Strategi Sir Basil Liddell Hart - Hana Putra; Djayeng Tirto; Bambang Wahyudi; Pujo Widodo (Journal on Education, 2024)
The leadership of Vladimir Putin has been the subject of intense debate in the context of Russian defense policy. By integrating the theory of Sir Basil Liddell Hart, this review aims to examine Putin's role and influence in the formation and implementation of Russian defense policy. This research is qualitative with a descriptive design, where data sources are drawn from literature, online media, journals, and relevant print books. The findings of this study indicate that by exploring Russian defense policy under Vladimir Putin's authoritarian leadership, there has been a significant improvement in both the economy and defense sectors, projecting Russia onto the world stage. However, it is noted that certain aspects, such as the failure of its air power and the need for new strategies to confront modern Ukrainian air capabilities, require attention from Vladimir Putin. The conclusion drawn is that authoritarian leadership does not guarantee smooth outcomes, as evidenced by failures in air defense. The concept of "grinding meat" is a concept that still needs to be considered, suggesting that greater use of unmanned technology would be preferable to minimize casualties.